2009
DOI: 10.1007/s10198-009-0168-z
|View full text |Cite
|
Sign up to set email alerts
|

A review of studies mapping (or cross walking) non-preference based measures of health to generic preference-based measures

Abstract: HHe ea al lt th h E Ec co on no om mi ic cs s a an nd d D De ec ci is si io on n S Sc ci ie en nc ce e D Di is sc cu us ss si io on n P Pa ap pe er r S Se er ri ie es s No. 08/02A review of studies mapping (or cross walking) from non-preference based measures of health to generic preference-based measures INTRODUCTIONA common approach to assessing the outcomes of health care is to obtain patient reported descriptions of health status across various dimensions and then to apply a standardised numerical scoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

59
646
6
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 424 publications
(714 citation statements)
references
References 35 publications
59
646
6
3
Order By: Relevance
“…That review article excluded mapping algorithms targeted at other generic preference-based outcome measures that can generate health utilities, such as the SF-6D [46] and the Health Utilities Index (HUI) [47], which have been the target of numerous other mapping algorithms (e.g. [1,42,[48][49][50][51][52]). Moreover, the popularity of the mapping approach for estimating health utilities is unlikely to wane given the numerous contexts within health economic evaluation where primary data collection is challenging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That review article excluded mapping algorithms targeted at other generic preference-based outcome measures that can generate health utilities, such as the SF-6D [46] and the Health Utilities Index (HUI) [47], which have been the target of numerous other mapping algorithms (e.g. [1,42,[48][49][50][51][52]). Moreover, the popularity of the mapping approach for estimating health utilities is unlikely to wane given the numerous contexts within health economic evaluation where primary data collection is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical models used in mapping studies can be categorised into ''direct'' methods (onto index or utility scores) and ''indirect'' or ''response mapping'' methods (onto dimensions responses). There are clear advantages and disadvantages of each method and of different estimators, but clear guidance about which to use in different circumstances is lacking [1]. Therefore, authors should provide sufficient information about their modelling approach(es) so that readers can assess the robustness of their overall estimation strategy.…”
Section: Item 10: Modelling Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide variety of predictor variables have been mapped in different illnesses 34 . In rheumatic diseases, the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) has been mapped to the UK EQ-5D 35,36 and the HUI-3 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Head-to-head comparisons were identified in 392 studies, suggesting low level of agreement, and hence a need for developing algorithms to compare utility scores across the various instruments used. Crosswalks or 'mappings' between a disease specific instrument and a HSU-instruments are commonly used to enable QALY estimations [6,7]. However, while such crosswalks between HSU-instruments are rare [8][9][10][11], previous studies have indicated non-linear relationships [8,9,11].…”
Section: Introductionmentioning
confidence: 99%